Solid waste collection and management practices among community residents in varying population density areas in Ibadan, South West Nigeria (2014)
This paper presents the results of a study conducted in four socio-economic (three urban low-, medium- and high-density residential communities and one rural) areas of Ibadan. The study assessed the amount and nature of solid waste generated the level and benefits of community participation in source separation and recycling potential and the factors responsible for poor solid waste management in the city. The study is cross sectional in design involving 153 households. A questionnaire survey and waste assessment were carried out in the selected households. Waste assessment included volume, weights and various segregated waste components over a period of seven days in the week. The waste generated (kg/c/day) was the highest in low density area (0.688) followed by rural (0.636), high density (0.452) and medium density area (0.303). The mean generation rate was 0.52 Kg/c/day. The recyclable dry waste was more than the wet waste. About 71.7% of the respondents were aware of and segregated some recyclables from the wastes and only 9.2% tried to convert wet waste into compost. The reasons for non-practice of source separation of waste at household level were bad odour, lack of capital, fear of disease-causing germs, pollution of surroundings, and need for much labour and time. The study suggested creation of more awareness along with demonstration/practice of waste assessment, regular segregation and recycling activities involving stakeholders in the communities.